Relative variability in muscle activation amplitude, muscle oxygenation, and muscle thickness: Changes with dynamic low-load elbow flexion fatigue and relationships in young and older females. (August 2021) - Bailey, Christopher A.; Yoon, SangHoon; Côté, Julie N.
Abstract: In repetitive upper limb activities, variability of muscle activity (a feature of motor variability) is linked to upper limb fatigability. Prior studies suggest that the variability response may change with age and could be related to the oxygen saturation of hemoglobin within the muscle. We determined, in female adults, how age affects adjustments in movement-to-movement variability of electromyograph (EMG) amplitude (RMS), oxygenation, and thickness with fatigue, and explored how these responses were related. Fifteen young (23.3 ± 3.1 years) and ten older (62.8 ± 6.9 years) females completed repeated trials of low-load, isokinetic, concentric/eccentric elbow flexion until maximal torque ≤ 70% of baseline. Movement-to-movement variability of EMG RMS in concentric phases of movement was quantified by the coefficient of variation (EMG CV), and muscle oxygenation and thickness (MTH) were quantified using near-infrared spectroscopy, and B-mode ultrasonography. Age*Time and Spearman ρ analyses were conducted. Age did not affect fatigability or Time-related changes in muscular measures (p > 0.05). Biceps brachii and brachialis EMG CV decreased, biceps brachii HbO2 decreased and did not fully recover, and biceps brachii and brachialis MTH increased. Higher initial brachialis EMG CV was related to less blunted oxygenation in young females (p = 0.021). Oxygenation responses were related to altered anterior deltoid EMG CV in young females but altered biceps brachii and brachialis EMG CV in older females. Age was not associated with changes in EMG CV, oxygenation, or thickness at similar performance fatigability in the concentric/eccentric elbow flexion task studied. Adjustments in biceps brachii oxygenation were linked to changes in EMG CV more local to the site of fatigue with older age.